Consumer preferences for operator collaboration in intra- and intercity transport ecosystems: Institutionalising platforms to facilitate MaaS 2.0. (June 2022) - Bushell, James; Merkert, Rico; Beck, Matthew J.
Abstract: The presence of institutional mechanisms to facilitate collaborative activities between operators, and consumer preferences for these activities, have not been studied in the public transport context. Exploring preferences in both intracity and intercity transport options (incorporating long distance transport components such as air services), we use random parameters logit models to analyse integrated travel choice experiments. We show that consumers have preferences for attributes resulting from operator collaboration that can deliver them better door-to-door travel options across the whole transport ecosystem, both in their own city but just as importantly, when travelling to another city. Our results suggest that the proposed method of institutional integration (MaaS 2.0 or CaaS) creates better value for respondents, such that they would be more likely to engage with integrated transport solutions rather than the default option for many, which is the car. Consumers are willing to pay for collaboration activities that inherently arise out of institutionally facilitated interaction between operators and that lead to improvements in their journey. Expansion of institutional integration such as that which may be possible through smart ticketing platforms as an institutional coordination mechanism may facilitate greater development of these features and lead to more integrated travel being chosen by consumers.